Syntactic structure of Spanish parasynthesis: towards a split little-v via affectedness - Gabriel Antonio Martínez Vera (Universitat Autònoma de Barcelona, 2016)
In this paper, I claim that the syntactic structure of Spanish parasynthetic verbs a-…-ar (e.g. a-bland-ar ‘to soften’) and en-…-ar (en-dulz-ar ‘to sweeten’) provides (further) evidence for a decomposed vP structure. I propose that these verbs are represented with a structure where v.Caus and verbalizer-v are distinct. In particular, I analyze transitive a-/en-…-ar verbs as complex predicates with a v.Caus-headed vP and a Small Clause (SC) that denotes change of state/location for the theme. These verbs differ in the properties of a projection (XP), located between vP and SC, whose head expresses how specific the result state/location for the internal argument is: a-...-ar specifies a (particular) result state/location for the internal argument whereas en-...-ar remains underspecified with regard to a (particular) result state/location.